Survey on Parenting Patterns and Information Technology Use on Students’ Language Development of Ikal Iqra Kindergarten of Padang City - Hidayatul Khairati; Delfi Eliza (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
Parenting patterns are very decisive and influence aspects of early childhood development, especially aspects of children's language development. Information technology is also an important aspect of the factors influencing children's language development. For this reason, this study aims to describe parenting patterns and the use of information technology on children's language development. This study used a quantitative descriptive method with 30 parents from Ikal Iqra Kindergarten in Padang City as respondents. The data collection technique used to collect parenting data and information technology on children's language development was a questionnaire. The instrument validation test employed Pearson's product-moment, while the reliability test utilized the Alpha Cronbach formula using SPSS 23. The results revealed the effect of parenting patterns on the language development of 30 children, of which five children had a good classification (16.7%), and 25 children had a very good language classification (83.3%). Meanwhile, for children's language development on the effect of using information technology, from 30 children, 23 children had a good classification (76.7%), and seven children had a very good classification (23.3%). Thus, it can be concluded that parenting patterns and the use of information technology affected the language development of Ikal Iqra Kindergarten children in Padang City.